Designing an Completeness Medical Record Document Website Using Waterfall Model - Anisa Rahayu; Lidia Putri Fitriana; Nurhayati; Ike Yunia Pasa (Proceeding of International Conference on Science, Health, And Technology, 2021)
The development of information technology makes aspects of life using computers. At Hidayah Hospital, Boyolali, the analysis of the completeness of medical record documents is still manual. This implementation raises the problem of the absence of a report on the results of the completeness analysis. In this case, the researcher conducted observations, interviews and literature studies on the assembling and reporting officer. From the process of inputting patient data, doctor data, ward data, form data and diagnostic data, processed with a website that analyzes the completeness of medical record documents then stored and produces output in the form of completeness analysis reports, incomplete performance reports and IMR and DMR reports. By using the waterfall method. The design uses the PHP programming language with Dreamweaver applications and MySQL databases.